ANALISIS GRAMATIKA VISUAL DALAM PEMAKNAAN POTRET PEREMPUAN PADA SAMPUL MAJALAH MANGLE - Rachminingsih, Irma; Sundari, Yupi (ATRAT: Jurnal Seni Rupa, 2022)
Visual grammatical analysis shows how the image maker chooses the available semiotic sources to form meaning and convey messages. Portraits are analyzed to reveal the representation, interaction, and composition meanings. In terms of representational meaning, the photo on the cover of Mangle shows a conceptual representation of carrier-possessive attributes. When we look at the photo, we associate long loose hair or buns, headpieces, accessories, kebaya and make-up with Sundanese women as a whole. The carrier is shown as a beautiful, feminine, motherly, friendly, and confident woman embracing Sundanese values. In terms of the interaction meaning, the analysis was carried out by considering aspects of contact, social distance and attitude. The eye contact of the model looking at the observer shows a demand in which the model seems to greet and demands the viewer to pay attention. Close-up shot indicates a close and personal relationship between the model and the observer, while medium long shot captures social distance.Keywords: visual grammar, female photo, Mangle cover.----------------------------------------------------------------------------------Analisis gramatika visual memperlihatkan bagaimana pembuat gambar memilih beragam sumber semiotika yang tersedia untuk membentuk makna dan menyampaikan pesan. Potret dianalisis untuk mengungkap makna representasi, interaksi, dan komposisi. Dari segi makna representasi, potret pada sampul Mangle menunjukkan representasi konseptual carrier-possessive attributes. Saat melihat potret, kita mengaitkan gaya rambut panjang terurai atau sanggul, hiasan kepala, aksesori, busana kebaya dan make-up dengan perempuan Sunda sebagai gambaran keseluruhan. Penyandang (carrier) yang ingin diungkapkan adalah Mangle sebagai sosok cantik, feminin, keibuan, ramah, percaya diri dan memegang nilai tradisi Sunda. Dari segi makna interaksi, analisis dilakukan dengan mempertimbangkan aspek kontak, jarak sosial dan sikap. Kontak mata model menatap pengamat menunjukkan demand, model seolah menyapa dan meminta pengamat memerhatikan. Pengambilan gambar close-up mengindikasikan relasi antara model yang dekat dan personal dengan pengamat, sedangkan pengambilan gambar medium long shot merealisaikan jarak sosial.Kata Kunci: gramatika visual, potret perempuan, sampul Mangle